Development and Quality Assessment of Functional Chicken Star - Nayak, N.K.; Pathak, V.; Bharti , S.K.; Goswami , M. (Journal of Meat Science, 2015)
The objective of this study was to evaluate the effect of carrageenan at different levels as fat replacer to develop functional chicken star. The physico-chemical, proximate and sensory quality of chicken meat star was evaluated. Results indicated that the pH, cooking yield, emulsion stability and moisture content was significantly (p
Keywords: Chicken star; Carrageenan; Fat replacer; Fun